Recém-nascidos pré-termo: critérios para a introdução da alimentação por via oral - Prade, Leila Sauer (2006)
The early assistance to the newborn presenting oral motor sensorial system dysfunction conveys to the sucking development prevents the compromising of his nutrition. The aim of this study was to determine the criteria to the introduction of feeding through mouth and its possible correlation to the preterm infant from the Neonatal Intensive Care Unit of the University Hospital of Santa Maria. A total of 32 preterm infants were enrolled in this study. Inclusion criteria were: gestational age under 37 weeks, the condition of being clinically stable, discharging the need of mechanical respiratory assistance, the absence of neurological problem neither alteration that could interfere in the oral function development it was also necessary to present the conditions to introduce the oral feeding. Concerning legal representation, informed consent was obtained from parents and/or legal representation. This study was approved by Federal University of Santa Maria research ethical committee. The speech-language evaluation included the data collection from the patient s file; regarding: way of delivering, gender, birth weight, gestational age and appropriate weight for sizing, chronological age, weight in the specific date, physical pattern, respiratory assistance, heart and respiratory rate, behavior state, oral reflections, oral motor sensorial characteristics. Aspects of non-nutritive and nutritive sucking were also considered, such as: number of sucking in the first three burst, time of sucking, time of pauses among the sucking burst, strength and rhythm; besides the swallowed volume throughout the feeding and its length. The results were analyzed at the STATA program version 5.0 (1998) using the parametric test Variance ANOVA and non parametric test of Mann-Whitney beyond chisquare analysis and Spearman s correlation with the value of p lower that 0,05. The results showed that the medical team uses the 34 weeks post conception age, weight about 1700g and clinically stable at the moment of their transition from tube to bottle feeds. The analysis pointed to the need of the existence of searching, sucking and swallow reflexes so that the preterm infant can be allowed to perform the non-nutritive and nutritive sucking presenting strength and rhythm Furthermore, significant differences were found in fast rhythm of sucking because it s allows organized sucking and guarantee the efficient ingestion of liquid.